2020
DOI: 10.3390/membranes10100254
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Framework for Optimizing a Sweeping Gas Membrane Distillation (SGMD)

Abstract: The present work has undertaken a meticulous glance on optimizing the performance of an SGMD configuration utilized a porous poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-co-HFP) membrane. This was carried out by conducting a systematic framework for investigating and optimizing the pertinent parameters such as sweeping gas flow rate, feed temperature, feed concentration and feed flow rate on the permeate flux. For this purpose, the Taguchi method and design of experiment techniques were harnessed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…It must be stressed that, in the published articles, the presented assessment of the influence of the process parameters on the SGMD course differs many times. Indeed, increasing the feed flow velocity most often significantly increased the permeate flux [10,15,17,20]; however, in other studies, a slight influence of this parameter was shown [14,18]. The gas temperature at the inlet to the module usually has little effect on the process performance [4,15,21], although its importance was shown in [4].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It must be stressed that, in the published articles, the presented assessment of the influence of the process parameters on the SGMD course differs many times. Indeed, increasing the feed flow velocity most often significantly increased the permeate flux [10,15,17,20]; however, in other studies, a slight influence of this parameter was shown [14,18]. The gas temperature at the inlet to the module usually has little effect on the process performance [4,15,21], although its importance was shown in [4].…”
Section: Introductionmentioning
confidence: 94%
“…The use of small SGMD modules for testing allows for very favourable yields, often above 20 L/m 2 h [15,16,18,20]. Unfortunately, similarly to large DCMD modules, increasing the process scale causes a multiple decrease in the permeate flux [4][5][6]13,23].…”
Section: Introductionmentioning
confidence: 99%
“…Based on Equation (16), assuming the feed heat losses in all four configurations are the same, it can be found that VMD should have the highest thermal energy efficiency, which is close to 100% since there is negligible thermal conduction loss. The permeate sides of both AGMD and SGMD are gas phase, but SGMD would have higher flux [ 78 ] and have comparable or lower thermal efficiency to AGMD [ 79 ]. The permeate side of DCMD is the liquid phase.…”
Section: Mechanism Of Heat Transfer and Mass Transfer Through Poromentioning
confidence: 99%
“…The Taguchi method was employed in the study of a systematic framework to test and optimize the performance of a sweep gas membrane distillation (SGMD) configuration in combination with a porous polyvinylidene fluoride-co-hexafluoropropylene (PVDF-co-HFP) membrane as reported by Nawras et al [32]. Another study used response surface methodology (RSM) to find the optimal conditions for the removal of brilliant green dye using a combination of photocatalysis and ceramic nanofiltration processes, researching the effect of pH, catalyst loading, and time duration variables on the response [33].…”
Section: Introductionmentioning
confidence: 99%